MENEGUHKAN KEMBALI TRADISI PESANTREN DI NUSANTARA - Hasani Ahmad Said (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article shows the unique tradition at Islamic boarding schoolwhich is always interesting to dicuss. Many prominent people were bornand come from boarding schools. Meanwhile, nowadays there are somecritiques toward this institution related to its polarization. It could beunderstood as a way to face the social changes and modernisation. Thiscondition, influence its existence, dynamics, and institution’s role. Bydoing a library research about pesantren history, the writer beleives thatpesantren would be able to survive without losing its identity.